Comparison of thermophilic and mesophilic anaerobic treatments for potato processing wastewater using a contact reactor - Ince, E.; Ince, M.; Engin, Onkal G. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
In this study, different organic loading rates (OLRs) ranging from 1.1 to 5.0 kg COD/m(3.)day were used to assess the performance of an anaerobic reactor at the optimum mesophilic (35 degrees C) and thermophilic (55 degrees C) temperatures. The methane gas production rate of the thermophilic treatment was higher than that of the mesophilic treatment. The efficiency of chemical oxygen demand (COD) removal was observed to range from 89.12 to 93.20% following the thermophilic anaerobic treatment and from 76.36 to 92.62% following the mesophilic treatment. The average VFA (volatile fatty acid)/alkalinity ratio of the effluent was 0.3 under both thermophilic and mesophilic conditions for all the OLR applications. The HPr/HAc (propionic acid/acetic acid) ratio was calculated as 0.16 and 1.3 for the mesophilic and thermophilic treatments, respectively. For the mesophilic treatment, the average methane gas production was found to be 0.394 m(3) CH4/kg CODremoved while it was 0.42 m(3) CH4/kg CODremoved for the thermophilic experiment. However, the sludge settleability of the mesophilic treatment was better than that of the thermophilic treatment.
Keywords: mesophilic; thermophilic; anaerobic treatment; wastewater; contact reactor; BIOHYDROGEN PRODUCTION; BED REACTOR; COMPARATIVE PERFORMANCE; CATTLE MANURE; SWINE MANURE; TEMPERATURE; DIGESTION; FILTERS; EFFICIENCY; OPERATION; Environmental Sciences & Ecology